A STUDY OF NINETY SNAKE BITE CASES AT PAKISTAN AIR FORCE (PAF) HOSPITAL, SHORKOT, PAKISTAN: Snake Bite Cases - Asif, Naveed; Akhtar, Farhan; Kamal, Khawar (Pakistan Armed Forces Medical Journal, 2015)
Objective: Analysis of clinico-epidemiological and laboratory findings of snake bite cases managed in PAF Hospital Shorkot. Study Design: Descriptive observational study. Place and Duration of Study: PAF Hospital Shorkot, from July 2008 to June 2011. Materials and Methods: A total of ninety (90) cases of snake bite who reported in emergency department of the hospital were included in the study. Data of patients was recorded for type of snake (as much as possible), site of snake bite, presence of fang marks, age and sex of the person bitten, date, time and place of bite, time taken by the victim to reach hospital, presence of symptoms and signs of envenomation in victim and type of treatment received before referral. All patients were managed accordingly. Similarly type of in- hospital treatment like giving of anti-venom serum and total duration of hospital stay in each patient was also recorded. Data was then expressed in percentage. Results: There were 70% male and 30% female patients. The age range was 7-54 years with a mean age of 27.8 +/- 10.8 years. Most of the cases of snake bite (82%) occurred between the months of April and September. A total of 60 (66.6%) patients were bitten at night. In 21 (23.3%) cases the victims brought the snakes. Among these, 4 (19.0 %) snakes were scaled vipers, 3 (14.3%) snakes were kraits and 2 (9.5%) snakes were cobras, while 57.2% snakes remained unidentified. Majority (63%) had bites on lower extremities, 36% had bites on upper limbs. One (1.1%) victim was bitten on scrotum. Intravenous anti-snake venom was given to 52 (57.8 %) patients Conclusion: Majority of cases of snake bite occur during rainy summer season in rural areas particularly at night. Severity and pattern of envenoming varies from patient to patient. Knowledge of types of snake and risk factors and complications of snake bite is important. Early evacuation of snake bite cases to nearest hospital capable of dealing with snake bite can effectively reduce mortality and morbidity.